Arthroscopic International Cartilage Repair Society Classification System Has Only Moderate Reliability in a Porcine Cartilage Repair Model. Issue 6 (May 2021) - Puhakka, Jani; Paatela, Teemu; Salonius, Eve; Muhonen, Virpi; Meller, Anna; Vasara, Anna; Kautiainen, Hannu; Kosola, Jussi; Kiviranta, Ilkka
Background: The International Cartilage Repair Society (ICRS) score was designed for arthroscopic use to evaluate the quality of cartilage repair. Purpose: To evaluate the reliability of the ICRS scoring system using an animal cartilage repair model. Study Design: Controlled laboratory study. Methods: A chondral defect with an area of 1.5 cm 2 was made in the medial femoral condyle of 18 domestic pigs. Five weeks later, 9 pigs were treated using a novel recombinant human type III collagen/polylactide scaffold, and 9 were left to heal spontaneously. After 4 months, the pigs were sacrificed, then 3 arthroscopic surgeons evaluated the medial femoral condyles via video-recorded simulated arthroscopy using the ICRS scoring system. The surgeons repeated the evaluation twice within a 9-month period using their recorded arthroscopy. Results: The porcine cartilage repair model produced cartilage repair tissue of poor to good quality. The mean ICRS total scores for all observations were 6.6 (SD, 2.6) in arthroscopy, 5.9 (SD, 2.7) in the first reevaluation, and 6.2 (SD, 2.8) in the second reevaluation. The interrater reliability with the intraclass correlation coefficient (ICC) for the ICRS total scores (ICC, 0.46-0.60) and for each individual subscore (ICC, 0.26-0.71) showed poor to moderate reliability. The intrarater reliability with the ICC also showed poor to moderate reliability for ICRS total scores (ICC, 0.52-0.59) and for each individual subscore (ICC, 0.29-0.58). A modified Bland-Altman plot for the initial arthroscopy and for the 2 reevaluations showed an evident disagreement among the observers. Conclusion: In an animal cartilage repair model, the ICRS scoring system seems to have poor to moderate reliability. Clinical Relevance: Arthroscopic assessment of cartilage repair using the ICRS scoring method has limited reliability. We need more objective methods with acceptable reliability to evaluate cartilage repair outcomes.